Penerapan Model Pembelajaran Group Investigation Menggunakan Strategi Bioedutainment untuk Meningkatkan Hasil Belajar Kognitif Mahasiswa - Nike Anggraini; Khoiron Nazip (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Bioedutainment strategies can be integrated with various methods, models, and approaches. The group inquiry learning model or group investigation is one approach that combines learning with bioedutainment techniques that can be used in biology learning. This study aims to determine student learning outcomes and activities after the application of the group investigation learning model using the bioedutainment strategy on the basic biology concepts. The research was carried out with the research sample being students of the Department of PGSD FKIP Sriwijaya University even semester 2021/2022, totaling 89 students. The sample was selected using a purposive sampling technique based on the research objectives. This type of research is pre-experimental with a one shot case study research design. Test instruments and observation sheets were used to analyze the data quantitatively which consisted of 20 multiple choice questions and 5 essays. The results showed that the average increase in student learning outcomes who achieved classical completeness was 84.90% for the Indralaya class and 91.17% for the Palembang class. This shows that student learning outcomes have reached the expected classical completeness of learning ≥ 80%.